Developing Terra Nullius: colonialism, nationalism, and indigeneity in the Andaman Islands - Sen, Uditi (Cambridge University Press, 2017)
This article explores in detail the legal structures and discursive framings informing the governance of one particular ‘backward’ region of India, the Andaman Islands. It traces the shifting patterns of occupation and development of the Islands in the colonial and post colonial periods, with a special focus on the changes wrought by independence in 1947 and the eventual history of planned development. It demonstrates how intersecting discourses of indigenous savagery/primitivism and the geographical emptiness was repeatedly mobilised in colonial era surveys and post-colonial policy documents. Post colonial visions of developing the Andaman Islands ushered in a settler-colonial governmentality, infused with genocidal fantasies of the ‘dying savage’. Laws professing to protect aboriginal Jarawas actually worked to unilaterally extend Indian sovereignty over the lands and bodies of a community clearly hostile to such incorporation. It questions the current exclusion of India from the global geographies of settler-colonialism and argues that the violent and continuing history of indigenous marginalisation in the Andaman Islands represents a de facto operation of a logic of terra nullius.